2017
DOI: 10.15640/jthm.v5n1a9
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant Employees’ Food Handling Practices in Irbid City, Jordan

Abstract: It has been established that food handlers working in foodservices are the main source of food borne outbreaks. The current study objective is to assess restaurant employees' food handling practices by exploring driving forces behind these practices. The study was accomplished quantitatively covering 245 restaurant employees in Irbid city-Jordan; who provided primary data by completing a designated self-administered questionnaire. A model of nine hypotheses was developed and examined using independent-samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
3
9
0
1
Order By: Relevance
“…The findings from the current study were further supported by a previous study in Jordan where FHs were found to be having a "very poor" to "good" knowledge in food handling operations [27]. Improved knowledge in addition to practices in this area has been associated with food handling training [17,21]. These findings emphasize the necessity of training of FHs in this regard.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The findings from the current study were further supported by a previous study in Jordan where FHs were found to be having a "very poor" to "good" knowledge in food handling operations [27]. Improved knowledge in addition to practices in this area has been associated with food handling training [17,21]. These findings emphasize the necessity of training of FHs in this regard.…”
Section: Discussionsupporting
confidence: 87%
“…Literature indicated that the reason why only a minority of hospital FHs attended a FS training course maybe attributed to underestimation of the importance of the FS, lack of hospitals' administrative support and commitment to involve them in the FS training sessions [50,51]. In line with most of the reported conclusions about the importance of FS training [17,52], findings from the current study supported the premise of this importance. The lack of FS training has been reported to be a reason behind an inadequate FSK, which, in turn, can result in unsafe food handling practices [53,54].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar result was obtained by Simsek et al, (2009) who found that (299) food handlers in Sanliurfa, in South-eastern Anatolia are males because the majority of women in Southern Anatolia are unemployed. Habiballah et al, (2017) found that majority of workers (81.6%), who are working in tourist restaurants in Irbid, Jordan were males; they found that females are not eager to work in restaurants (Kasturwar and Shafee 2011). Other studies revealed that their samples are mixed near to equal percentages (Kasturwar and Shafee 2011;El-Shenawy et al, 2014;Castro et al, 2016).…”
Section: Demographic Characteristics Of Food Handlersmentioning
confidence: 99%
“…Furthermore, most of them were carried out on households' food handling practices. In Jordan, in spite there were some studies that investigated food handlers' practices including Osaili et al (2011), Sharif et al (2013), Osaili et al (2013), Habiballah et al (2017) and Habiballah et al (2018), they were focusing on the demographics and/or knowledge and attitudes of food handlers. Accordingly, it can be seen clearly that there is a gap in applying the HBM on professional food handling practices.…”
Section: Introductionmentioning
confidence: 99%